A screening on Specific Learning Disorders in an Italian speaking high genetic homogeneity area. (October 2015) - Cappa, Claudia; Giulivi, Sara; Schilirò, Antonino; Bastiani, Luca; Muzio, Carlo; Meloni, Fabrizio
Highlights: We investigate the prevalence of SLD in a high genetic homogeneity area. The 68.7% of all second grade pupils ( n  = 610) of the area took part in the study. We found a prevalence of 6.1% of pupils with SLD. 82.8% of them manifested dyslexia. Our results underline the influence of the genetic component in the prevalence of SLD. Abstract: The aim of the present research is to investigate the prevalence of Specific Learning Disorders (SLD) in Ogliastra, an area of the island of Sardinia, Italy. Having experienced centuries of isolation, Ogliastra has become a high genetic homogeneity area, and is considered particularly interesting for studies on different kinds of pathologies. Here we are going to describe the results of a screening carried out throughout 2 consecutive years in 49 second grade classes (24 considered in the first year and 25 in the second year of the study) of the Ogliastra region. A total of 610 pupils (average age 7.54 years; 293 female, 317 male) corresponding to 68.69% of all pupils who were attending second grade in the area, took part in the study. The tool used for the screening was "RSR-DSA. Questionnaire for the detection of learning difficulties and disorders", which allowed the identification of 83 subjects at risk (13.61% of the whole sample involved in the study). These subjects took part in an enhancement training program of about 6 months. After the program, pupils underwent assessment for reading, writing and calculation abilities, as well as cognitive assessment. According to the results of the assessment, the prevalence of SLDs is 6.06%. For what concerns dyslexia, 4.75% of the total sample manifested this disorder either in isolation or in comorbidity with other disorders. According to the first national epidemiological investigation carried out in Italy, the prevalence of dyslexia is 3.1–3.2%, which is lower than the prevalence obtained in the present study. Given the genetic basis of SLDs, this result, together with the presence of several cases of SLD in isolation (17.14%) and with a 3:1 ratio of males to females diagnosed with a SLD, was to be expected in a sample coming from a high genetic homogeneity area.